PEMELIHARAAN BANDENG KAWAK UNTUK FESTIVAL LELANG BANDENG KABUPATEN SIDOARJO SEBAGAI PEMBELAJARAN KONTEKSTUAL BERBASIS PROYEK - Ulimawati, Yetti; Supriyono, Supriyono; Rahayuningsih, Sri (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The Milkfish Auction is a unique program from Sidoarjo Regency, based on a combination of coastal community traditions and traditional Islamic values. This program is held annually by the community to commemorate the Prophet Muhammad's birthday, with the primary goal of increasing economic growth and community religiosity. The Kawakan Milkfish Auction tradition, which has been held since 1962 in Sidoarjo, is a local initiative that combines economic, cultural, and social values in the management of fishery resources. This study aims to examine the contribution of this tradition to fisheries conservation and the sustainability of aquatic ecosystems. Using a qualitative approach through literature review and interviews with fish farmers and local communities, it was found that this auction not only improves economic well-being but also encourages sustainable fishing practices. Community participation in the auction strengthens social bonds and awareness of the importance of preserving natural resources, particularly milkfish, a symbol of local wealth. Furthermore, the implementation of sustainable cultivation and waste management helps minimize environmental impacts. This tradition also has the potential to increase the competitiveness of milkfish products, attract investment, and create long-term economic opportunities for coastal communities ABSTRAK Lelang Bandeng merupakan sebuah program unik dati Kabupaten Sidoarjo yang didasarkan pada perpaduan tradisi masyarakat pesisir dan nilai-nilai Islam tradicional. Program ini diadakan oleh masyarakat setiap tahun untuk memperingati Maulid Nabi Muhammad dengan mencapai tujuan utama meningkatkan pertumbuhan ekonomi dan religiunitas masyarakat. Tradisi Lelang Bandeng Kawakan yang telah berlangsung sejak 1962 di Sidoarjo merupakan inisiatif lokal yang menggabungkan nilai ekonomi, budaya, dan sosial dalam pengelolaan sumber daya perikanan. Penelitian ini bertujuan untuk mengkaji kontribusi tradisi tersebut terhadap konservasi perikanan dan keberlanjutan ekosistem perairan. Dengan pendekatan kualitatif melalui studi literatur dan wawancara dengan petani tambak dan masyarakat lokal, ditemukan bahwa lelang ini tidak hanya meningkatkan kesejahteraan ekonomi, tetapi juga mendorong praktik perikanan berkelanjutan. Partisipasi masyarakat dalam lelang memperkuat ikatan sosial dan kesadaran akan pentingnya menjaga sumber daya alam, khususnya ikan bandeng sebagai simbol kekayaan lokal. Selain itu, penerapan budidaya berkelanjutan dan pengelolaan limbah turut memperkecil dampak lingkungan. Tradisi ini juga berpotensi meningkatkan daya saing produk bandeng, menarik investasi, dan menciptakan peluang ekonomi jangka panjang bagi masyarakat pesisir.